2019
DOI: 10.1136/bmjopen-2018-022927
|View full text |Cite
|
Sign up to set email alerts
|

Association between gaps in antihypertensive medication adherence and injurious falls in older community-dwelling adults: a prospective cohort study

Abstract: ObjectiveGrowing evidence suggests that older adults are at an increased risk of injurious falls when initiating antihypertensive medication, while the evidence regarding long-term use of antihypertensive medication and the risk of falling is mixed. However, long-term users who stop and start these medications may have a similar risk of falling to initial users of antihypertensive medication. Our aim was to evaluate the association between gaps in antihypertensive medication adherence and injurious falls in ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…This observed association is similar to a prospective cohort study of 938 patients of community pharmacies in Ireland, whereby each 5-day gap in antihypertensive medication adherence increased the risk of self-reported falls by 18%. 32 It is possible that being adherent to antihypertensive medications may have reduced BP variability in patients, which led to the observed reduction in the risk of falls. 33 Alternatively, those who adhered to their medications may have also participated in other healthy behaviors (eg, regular physical activity, healthy diet and regular healthcare attendance) which contributed to fewer observed falls.…”
Section: Discussionmentioning
confidence: 99%
“…This observed association is similar to a prospective cohort study of 938 patients of community pharmacies in Ireland, whereby each 5-day gap in antihypertensive medication adherence increased the risk of self-reported falls by 18%. 32 It is possible that being adherent to antihypertensive medications may have reduced BP variability in patients, which led to the observed reduction in the risk of falls. 33 Alternatively, those who adhered to their medications may have also participated in other healthy behaviors (eg, regular physical activity, healthy diet and regular healthcare attendance) which contributed to fewer observed falls.…”
Section: Discussionmentioning
confidence: 99%
“…Although consecutive recruitment involves non-probabilistic sampling, it provides structured recruitment ensuring all participants can be enrolled, thus producing a more representative sample of the target population than convenience sampling. 26 27 Furthermore, the use of POSAMINO criteria, which focus on potentially serious alcohol–medication interactions, avoids overestimating risk by excluding those interactions, which are of limited clinical significance. In addition, medication use was evaluated objectively using pharmacy dispensing records.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical trials often exclude the frailest among the older population, who are at particular risk for falls and fractures. While chronic use of antihypertensives was not associated with falls in older people (OR 0.97 [0.93–1.01]) [ 25 ], several studies reported increased risk for falls [ 26 ] and injurious falls [ 4 , 5 ] when initiating or re-starting antihypertensives in long-term users after short treatment breaks [ 29 ]: Gribbin and colleagues [ 26 ] assessed the risk for a first fall in the 21 days following antihypertensive treatment initiation using SCCS in older UK patients. Increased fall risk was reported for thiazide diuretics (IRR 1.63 [1.20–2.20]), but not for other antihypertensive drug classes.…”
Section: Discussionmentioning
confidence: 99%